72 Primary care coding and psychotropic prescribing in young cancer survivors: mental health morbidity misclassification and implications for brain tumour survivorship - Emanuela Molinari; Valentina Fenech (Neuro-Oncology, 2026)
Abstract Introduction Survivors of childhood, teenage and young adult (CTYA) brain tumours experience higher rates of depression and anxiety than other CTYA cancer survivor groups. As secondary care data alone underestimate this burden, we evaluated whether integrating primary care and psychotropic prescribing data improves measurement of mental health morbidity in young cancer survivors. Method We linked secondary care, primary care and prescribing data via DataLoch for 8,862 five-year cancer survivors diagnosed before 40 years of age and 26,586 comparators matched on sex, age and socioeconomic deprivation in the Lothian region. The cohort included 489 brain tumour survivors. We examined first psychotropic prescriptions for antiseizure drugs, anxiolytics and hypnotics, antidepressants, antipsychotics, and drugs used in substance dependence. We cross-referenced these with GP coding to distinguish mental health from non-mental health use. Proportions were compared between groups. Results Among antiseizure and antidepressant users, survivors (n = 1,053 and n = 2,419) had mental health indications in 26.3% and 46.6% of cases, compared with 43.6% and 56.7% among comparators (n = 1,975 and n = 5,199). Antipsychotics (n = 382 survivors; n = 687 comparators) were used predominantly for psychosis (>90%). Anxiolytics and hypnotics (n = 1,724 survivors; n = 3,385 comparators) and drugs used in substance dependence (n = 623 survivors; n = 1,328 comparators) showed no evidence of alternative indications. After excluding non-mental health use, approximately 90% of first mental health events in both groups were identified through GP and prescribing (n = 2,667 survivors; n = 6,094 comparators), while hospital admissions accounted for fewer than 10%. Conclusions Mental health burden is largely identified and managed in primary care. Linking GP coding with prescribing improves measurement of mental health morbidity and minimises misclassification due to prescribing for alternative indications. This approach is particularly relevant for brain tumour survivors, who have been reported to experience higher burden.